Critical aortic stenosis presenting as STEMI - Ying X Gue; Sanjay S Bhandari; Damian J Kelly (Echo Research and Practice, 2017)
A 73-year-old male was brought into hospital with chest pain and inferior ST elevation on ECG. The patient immediately proceeded to the catheter lab for primary percutaneous coronary intervention. Angiography did not identify any culprit lesions to account for the patient’s electrocardiographic changes and ongoing symptoms of chest pain. Bedside echocardiography revealed critical aortic stenosis. Intra-aortic balloon pump (IABP) was inserted, resulting in resolution of chest pain and ST-segment changes. The patient underwent successful aortic valve (AV) replacement without the need for coronary intervention. This is a rare presentation of critical aortic stenosis (AS) presenting as ST-segment elevation myocardial infarction (STEMI).